Sociophilosophical concept of Duḥkha in Dhammapada and Yoga Sutra: A comparative study - Arvind Kumar Yadav; Tikhe Sham Ganpat (Wolters Kluwer Medknow Publications, 2021)
Duḥkha (Pāli: Dukkha) is an important concept in Dhammapada and Yoga, commonly translated as "suffering," "unhappiness," "pain," or "stress." It is universal and unavoidable. Dhammapada is the essence of Lord Buddha's teachings intended to guide the students of Yoga marga. It consists of 26 chapters and 423 verses in the Pāli language. There are many verses in Dhammapada which talk about the prevention and cure of Duḥkha. Dhammapada suggests not to do unwholesome action which causes Duḥkha and instructs to follow the Yoga Mārga (Dhamma): Śṭla, Samādhi, and Pragyā. Each one is responsible for their actions and consequences. The disciple should be mindful and involve in doing wholesome action with the right thought. Then they will be able to free from Duḥkha and may attain happiness (Nibbāna). The Yoga Sutra of Patañjali is well-known text among the Yoga fraternity. Sage Patañjali codified the knowledge of Yoga in a unique way and has mentioned some Yogic practices to be from Duḥkha and attain the state of liberation (Kaivalya). Both Yoga Sutra and Dhammapada emphasize that one can overcome Duḥkha through the development of understanding. However, the two philosophies widely differ in the nature of that understanding. Dhammapada emphasizes the understanding of Anatta (Anatman, nonself, nonsoul), and Yoga Sutra emphasizes the understanding of Svarupa (self, soul), as each discusses the means to liberation from Duḥkha. This paper reviews the concept of Duḥkha and its cessation in the light of Dhammapada and Yoga Sutra of Patañjali.